The imprint of hot spots on magnetized Kerr accretion disks: probing the cosmic censorship conjecture - Ranea Sandoval, Ignacio Francisco (2015)
In general relativity, black holes are uniquely described by the Kerr metric and, according to the cosmic censorship conjecture, curvature singularities are always hidden behind an event horizon. We study the effect of an external magnetic field on the observed light curves of orbiting hot spots in thin accretion disks in Kerr spacetimes with (black holes) and without (super-extreme solutions) horizons. We employ a ray-tracing algorithm to calculate the light curves and power spectra of such hot spots for uniform and dipolar magnetic field configurations and show that the presence of a dipolar magnetic field produces potentially observable signatures which might be useful to probe the nature of compact objects and to test the cosmic censorship conjecture.